Att skapa berättelsen och sig själv. Den självmedvetne berättaren och hans narrativa identitet i "Huset vid Flon" av Kjell Johansson - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2020)
The article’s aim is to discuss the Swedish autobiographical novel Huset vid Flon by Kjell Johansson as an example of the self-conscious narration (in Wayne C. Booth’s understanding). The grown-up narrator, who admits to being a professional writer, presents a retrospective of his childhood on Stockholm suburbs in the 1940s and 50s. He constructs his narration before the reader’s eyes, involves him/her in a dialogue, explains the employed narrative devices and plays the role of a guide through a no longer existing world. He is also an insightful and at times ironic commentator of the reality. For him organising the memories is above all a quest for his own identity. This “telling stories of oneself”, which can be viewed in a light of Paul Ricoeur’s narrative identity, is also strongly embedded in a collective experience of growing up in the Swedish welfare state.